2008
DOI: 10.1021/jp8055784
|View full text |Cite
|
Sign up to set email alerts
|

Soft-landing Isolation of Gas-phase-synthesized Transition Metal−Benzene Complexes into a Fluorinated Self-assembled Monolayer Matrix

Abstract: Gas-phase-synthesized chromium−benzene 1:2 sandwich cation complexes [Cr+(benzene)2] were soft-landed on a self-assembled monolayer (SAM) of fluorinated alkanethiol (C10F-SAM) at a hyperthermal collision energy of ∼20 eV. The adsorption properties and thermal stability of the soft-landed complexes were studied with infrared reflection absorption spectroscopy (IRAS) and temperature-programmed desorption (TPD). The landed complexes were neutralized due to charge transfer from the SAM substrate, but their native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 68 publications
4
33
0
Order By: Relevance
“…Deposition of polyatomic ions onto surfaces with retention of charge was reported by the same group 20 years later . Subsequent studies have shown that complex ions including peptides, proteins, organometallic complexes, and metal clusters , may be soft landed onto substrates intact. For example, previous studies from our laboratory examined the charge reduction and neutralization of protonated peptides ions , , as well as cationic metal–salen , and ruthenium tris(bipyridine) , organometallic complexes soft landed onto different SAMs.…”
Section: Introductionmentioning
confidence: 89%
“…Deposition of polyatomic ions onto surfaces with retention of charge was reported by the same group 20 years later . Subsequent studies have shown that complex ions including peptides, proteins, organometallic complexes, and metal clusters , may be soft landed onto substrates intact. For example, previous studies from our laboratory examined the charge reduction and neutralization of protonated peptides ions , , as well as cationic metal–salen , and ruthenium tris(bipyridine) , organometallic complexes soft landed onto different SAMs.…”
Section: Introductionmentioning
confidence: 89%
“…This intact deposition of projectile ions impinging on surfaces at low collision energies (<100 eV) was referred to as soft-landing, and this process may occur with or without retention of the initial ion charge [2][3][4]. Experiments of soft-landing have involved a wide variety of projectile ions, including small and medium-size polyatomic ions [1,[5][6][7][8][9][10][11][12], clusters [13][14][15][16][17][18][19][20][21][22][23][24], peptides [11,23,[25][26][27][28][29][30], proteins [25,31,32], a nucleotide [33], and intact viruses [34,35]. SAMs were used in many of these experiments because their well-characterized structure, controllable surface properties and biocompatibility make them convenient targets for biological and medical applications [36].…”
Section: Introductionmentioning
confidence: 99%
“…The intensities of IR peaks are almost the same as that on Au 25 :SC12 on a bare Au(111) substrate, although the transfer substrate is changed to a hydrophobic nature of F-SAM, on Au(111). Indeed, water contact angles of Au(111) and F-SAM are 0 and ∼112°, respectively. However, the result shows that the transfer ratio of the number of Au 25 :SC12 is not improved by the F-SAM.…”
Section: Resultsmentioning
confidence: 99%